Diagnosis and inflammatory response of patients with candiduria. Issue 1 (10th May 2012) - Helbig, S.; Achkar, J. M.; Jain, N.; Wang, X.; Gialanella, P.; Levi, M.; Fries, B. C.
Summary Candiduria is common in hospitalised patients, but the clinical relevance is still unclear. This study was done to further our knowledge on detection of and host responses to candiduria. Urines and clinical data from 136 patients in whom presence of yeast was diagnosed by microscopic urinalysis were collected. Diagnosis by standard urine culture methods on blood and MacConkey agar as well as on fungal culture medium (Sabouraud dextrose agar) was compared. Inflammatory parameters (IL‐6 and IL‐17, Ig) were quantified in the urine and compared with levels in control patients without candiduria. Standard urine culture methods detected only 37% of Candida spp. in urine. Sensitivity was especially low (23%) for C. glabrata and was independent of fungal burden. Candida specific IgG but not IgA was significantly elevated when compared with control patients (P < 0.0001 and 0.07 respectively). In addition, urine levels of IL‐6 and IL‐17 were significantly higher in candiduric patients when compared with control patients (P < 0.001). Multivariate analysis documented an independent association between an increased IgG (odds ratio (OR) 136.0, 95% confidence interval (CI) 25.7–719.2; P < 0.0001), an increased IL‐17 (OR 17.4, 95% CI 5.3–57.0; P < 0.0001) and an increased IL‐6 level (OR 4.9, 95% CI 1.9–12.4; P = 0.001) and candiduria. In summary, our data indicate that clinical studies on candiduria should include fungal urine culture and that inflammatory parameters may be helpful to identify patients with clinically relevant candiduria.